Loneliness and Information Communication Technology (ICT) in Adolescents - Linda Ernawati Erawan; Rina Sari (Universitas Muhammadiyah Banjarmasin, 2021)
Information and communication technology (ICT) is an important part of teenagers' lives. In addition to keeping them connected to the social environment, especially in the COVID-19 pandemic situation, ICT makes it easier for teenagers to get the various information they need. This study aims to look at the differences in the use of ICT (online games, information search, communication, and internet surfing) in adolescents aged 13-15 years based on gender, and to see the differences in loneliness that may be experienced by teenagers in the COVID-19 pandemic situation due to reduced social interaction with peers. The research sample amounted to 55, consisting of 23 men and 32 women using the Perth A-Loneness Scale (PALs) measuring instrument. Hypothesis testing was done by t-test, it was found that there was no significant difference in the use of ICT based on gender (P-value 0.471). Boys show intensity in the use of online games, while girls are more intensive in the use of communication. Loneliness test results show that there is a significant difference (P-value 0.049). From the results of the study, adolescent girls more often feel alone than boys even though they feel part of a group of friends, girls have a positive attitude towards loneliness, while boys are the opposite.